1999
DOI: 10.5006/1.3284044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Parameters on Passivation of Zirconium and the Stability of the Anodic Oxide Film

Abstract: Passivation of the zirconium surface and stability of anodic oxide film were investigated as a function of surface preparation. The mechanically polished surface appeared to be more reactive toward oxide thickening than the etched one, as revealed by impedance measurements. Oxide film formed on the etched electrode dissolved faster than that formed on the mechanically polished one. This was attributed to the increase of structural defects within the oxide film formed on the etched surface. Dissolution of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…These unexpected results demonstrate that the pretreatment applied to Zr prior to the formation of colored passive layers by ac polarization has a profound impact on its dissolution in an aqueous NaCl solution. These results agree with those obtained by Mogoda and others, , who found that chemically etched Zr experienced a greater dissolution rate than polished Zr.…”
Section: Resultssupporting
confidence: 93%
“…These unexpected results demonstrate that the pretreatment applied to Zr prior to the formation of colored passive layers by ac polarization has a profound impact on its dissolution in an aqueous NaCl solution. These results agree with those obtained by Mogoda and others, , who found that chemically etched Zr experienced a greater dissolution rate than polished Zr.…”
Section: Resultssupporting
confidence: 93%
“…For the three pH values studied (4.9; 5.2 and 5.6), the oxide layer is thinner for the polished specimens than for the unpolished and cold worked specimens, which appears to be consistent with the data reported in the literature [1,9,18,19]. However at pH = 4.9 (Fig.…”
Section: Effect Of Surface Finish and Thermal Treatment On Corrosion supporting
confidence: 92%
“…Mogada reported that ¤ oc increased with time for either mechanically polished or chemically etched zirconium electrode, which indicated oxide film thickening. 10 Similar behavior for metal Ti in a methanol solution was also observed by Qin et al 17 The oxide passivation in an anhydrous n-butanol solution is possibly due to the presence of undissociated acid molecules, which undergoes decomposition on zirconium surface and provides oxygen. 18,19 The addition of a small amount of water, as little as 0.1%, into the n-butanol solution seems to improve the protection characteristic of zirconium oxide.…”
Section: Open-circuit Potentialsupporting
confidence: 70%
“…Usually the passive film exhibits duplex nature with an external hydrated zirconium dioxide ZrO 2 ·nH 2 O layer (amorphous or strongly defective) and an internal anhydrous ZrO 2 layer. 10 It is deduced that water changes the passive film composition, microstructure and thickness, which decreases the affinity towards bromide ions as a result of occurrence of pitting corrosion at a more positive potential. The addition of 0.5% water is enough to form a layer of passive film.…”
Section: Cyclic Voltammetry Curvesmentioning
confidence: 99%
See 1 more Smart Citation